Pitfalls in TCR gene clonality testing: teaching cases - Groenen, Patricia J. T. A. (Springer-Verlag, 2008)
Clonality testing in T-lymphoproliferations has technically become relatively easy to perform in routine laboratories using standardized multiplex polymerase chain reaction protocols for T-cell receptor (TCR) gene analysis as developed by the BIOMED-2 Concerted Action BMH4-CT98-3936. Expertise with clonality diagnostics and knowledge about the biology of TCR gene recombination are essential for correct interpretation of TCR clonality data. Several immunobiological and technical pitfalls that should be taken into account to avoid misinterpretation of data are addressed in this report. Furthermore, we discuss the need to integrate the molecular data with those from immunohistology, and preferably also flow cytometric immunophenotyping, for appropriate interpretation. Such an interactive, multidisciplinary diagnostic model guarantees integration of available data to reach the most reliable diagnosis.